Principals' Decision-Making Strategies and Teachers' Job Satisfaction in Kwara State Schools, Nigeria - Olaifa, Adeseko Sunday; Odumosu, Faruq Ajobi; Alao, Monsurat Iyabo; Ibrahim, Hafiz Babajide; Sagaya, Abiodun Amudalatu (EduBase : Journal of Basic Education, 2025)
Objective: This study aimed to examine the relationship between principals' decision-making strategies and teachers' job satisfaction in secondary schools in Kwara State, Nigeria. Novelty: This study provides a unique perspective by analyzing multiple decision-making strategies, including open-door, closed-door, consultation, and collaboration, and their varying impacts on teachers' job satisfaction, which has not been extensively explored in the Nigerian secondary school context. Methods: This study used a descriptive survey design. It involved 7675 senior secondary school teachers from 407 public schools in Kwara State. A sample of 297 respondents was selected from 825 teachers using Krejcie and Morgan's table and simple random sampling from 35 schools. Data were collected through a self-designed questionnaire, "Principals' Decision-Making Strategies Teachers' Job Satisfaction Questionnaire" (PDMSTJSQ), on a 4-point Likert scale. Research questions were analyzed using mean and standard deviation, while hypotheses were tested using Pearson Product Moment Correlation at a 0.05 significance level. Results: The study found that open-door, closed-door, consultation, and collaborative decision-making strategies are the most common, with a mean of 3.18. Open-door decision-making positively correlates with teachers' job satisfaction, while closed-door and consultation strategies show negative correlations. Collaboration also has a negative relationship. These results suggest that teachers' job satisfaction is influenced by the decision-making strategies used and their overall work environment. Conclusion: The study found a significant relationship between open-door decision-making strategies, closed-door decision-making strategies, consultation decision-making strategies, and collaboration decision-making strategies in Kwara State secondary schools.